Effectiveness and Accountability of Local Budget (APBD) Financing: Evidence from Surabaya City (2020–2025) - Sari, Ratna Puspita; Oktaviana, Rosida Dwi; Athaillah, Ujung Imrhon; Djasuli, Mohamad Djasuli (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study aims to analyze the effectiveness and accountability of regional financing in Surabaya City during the 2020–2024 period, as well as the relationship between the two in public financial management. A descriptive quantitative approach was employed using effectiveness ratio analysis and accountability scoring. The results show that financing effectiveness fluctuated within a range of 72.4% to 108.2%, while accountability consistently improved from a score of 17 to 24 (very good category). The findings indicate that the two variables do not move linearly, as accountability remained high despite a temporary decline in effectiveness. This suggests a misalignment between performance and administrative accountability in regional financial management. The study highlights that accountability functions as a prerequisite for legitimacy but does not automatically ensure performance effectiveness. Therefore, a comprehensive evaluation of regional finance should simultaneously consider both dimensions to provide a more holistic assessment.